(3GdeSJOQc Ydi GdUMjMjfs - (3GdMGce GdfjSGHhQj , eMeO Hf YHO Gddg Hf MeOhjg Hf fYje GdVHj GdWgeGfj GdfjSGHhQj, CHh YHO Gddg, GdMGce, GHf GdHjY,J (B405 (3g` s
(3ChdgG (B:s
(3PcQ efGbH SYO Hf YHGOI s
(3BNQgG (B:s
(3BNQg eHJhQ, jfJgi CKfGA cJGH GdPHGFM , hBNQ eGajg (B: (3Yf Ce cQR hCHi cQR bGdG (B: (3fPQJ CeQCI ef Bd YHO GdQMef Hf CHj HcQ , hEf hdOJ CeQCI YHO GdQMef s
(3GdfSNI HgG MhGTs
(3JfHjI (B: (3hVY GdLRA GdSGOS bHd GdLRA GdNGeS ai GdJLdjO NWCs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B227 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B238s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdMOjK h GdeUWdMs